Pengaruh Indeks Harga Saham Luar Negeri Terhadap Indeks Harga Saham Gabungan (IHSG). - Budidarma, I Gusti Agung Musa (JBE (Journal of Business and Economics); Volume 11 No.1, 2012 JBE UNKLAB, 2012)
This study seeks to find out whether the movement of foreign stock indices are affecting the movement of Indeks Harga Saham Gabungan (IHSG). Population of this study are the stock price indices changes of Hang Seng Index, Kospi index, Nikkei index, ASX200 index, STI index, dan KLSE index. The findings indicate that Hang Seng index, Kospi index, Nikkei index, ASX200 index, and STI index have significant influence toward IHSG. Only KLSE index has no significant influence toward IHSG.